(untitled) (Economic Journal of Nepal, 2013)
There are two different views regarding utilization of remittance-one advocates remittance as giving rise to consumerism, the other claims it as a core agents in the development process. In Nepal, the two most reported uses of remittances received are: "for daily consumption" and "repayment of the loan". However, in general it is considered that international migration and remittances significantly reduce the level, depth, and severity of poverty in the developing world. Various studies shows that remittances help lift households out of poverty. This paper aims at exploring poverty reducing impact of the remittances income in some of the VDCs of Nepal using primary data. Three VDCs from hill, tarai and semi-urban areas of Nepal were selected for the study. Propensity Score Matching (PSM) approach was used to compare the status of the remittances receiving households (RRHH) with that of the remittances non-receiving households (RNRHH). The study assumes differences in the socio-economic status between the RRHH and the RNRHH as the visible and tangible impact of remittance on poverty reduction. For ascertaining the socio-economic differences in the selected VDCs, three broad indicators of people’s well-being: Economic Security; Human Development; and Empowerment and Social Inclusion were analyzed. Result of the analysis shows improved socio-economic status of the RRHH compare to the RNRHH in the study area. This enabled the RRHH in seeking good education, better health facilities/services. It can be hoped that if the RRHH continuously adopts foreign employment as their occupation and invest the remittance earning in productive sector, in the long run these investments will benefit changing attitude to realize standard of living.